Factors Contributing to Non-performing Financing: Evidence from Islamic Banks in Malaysia before Pandemic - Eni Noreni Mohammad Zain; Puspa Liza Ghazali; Wan Mohd Nazri Wan Daud (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This study is going to ascertain the contributing factor of non-performing financing in Islamic banks in Malaysia. Purpose – This study aims to investigate the specific bank characteristics as well as macroeconomic variables. Methodology/approach –Twelve local Islamic banks would be the focus for this study starting from period 2009 until 2018 which are before pandemic. The annual report has been used as the primary source for the financial data. While for the macroeconomics data, DataStream database has been used. Panel data approach was used to investigate the data and all the determining factor from both factors were regressed against non-performing financing. Findings – This study found that just two bank-specific characteristics, bank size and capitalization, showed a significant negative link with non-performing financing. While the other variables from macroeconomic factors does not give any important impact on non-performing financing for the Islamic banks in Malaysia.